Myths and truths: The law and finance Theory revisited - Michael Graff (ETH Zurich, KOF Swiss Economic Institute, 2006)
The law and finance theory predicts that the common law system provides the best basis for financial development and economic growth, followed by Scandinavian and German origin civil law and finally French origin civil law. Referring to a number of sceptical views, this paper argues that the theory faces an identification problem, since the majority of common law countries have a market-based financial system, whereas the majority of civil law countries have a bank-based financial system. Moreover, there are plausible alternative hypotheses to explain the quality of the financial system; but that they cannot rule out that the theory refers to a relevant link between the legal tradition and financial development. Finally it is argued that the corner stone of the law and finance theory is the proposition that different legal traditions imply different degrees of investor protection. It is demonstrated that a few minor, but sensible modifications in aggregating the original indicator set produce results that are different from those reported so far and contradictory to the theory's ranking of the four major legal families in terms of investor protection. Accordingly, the validity of the theory's investor protection measures for international comparisons, the supremacy of the common law legacy in protecting investors and, consequently, the validity of legal origin variables to instrument for financial development, have to be regarded as myths rather than truths.
Keywords: K22; G20; P00; 330; Financial Development; Legal System; Investor Protection; Wirtschaftswachstum; Finanzmarkt; Anlegerschutz; Rechtsordnung